The role of pharmacists in complementary and alternative medicine in Lebanon: users' perspectives - Mohamad Ali Hijazi; Hibeh Shatila; Zeina Omeich; Abdalla El-Lakany; Maha Aboul Ela; Farah Naja (BMC, 2021)
Abstract Background Customers' expectations and satisfaction are critical to ensure a more effective role of the community pharmacists in promoting the safe use of Complementary and Alternative Medicine (CAM). The aim of this study is to examine the perceptions and practices of customers buying their CAM products from pharmacies and explore their satisfaction with CAM-related services offered by the community pharmacists in Lebanon. Methods A national cross-sectional study was conducted among users of CAM (age > =18 years) who obtained their CAM from community pharmacies in Lebanon (n = 832). Within the proximity of the pharmacy, subjects were invited to complete a multi-component questionnaire. The latter consisted of four sections related to CAM: general beliefs, perception of pharmacists' role, practices, satisfaction with services offered by the pharmacists. In addition, the questionnaire included questions about sociodemographic characteristics of participants. Results The majority of participants agreed to an active role of the pharmacists' in guiding CAM use, however over half of the participants (61.3%) did not agree that the pharmacist is more knowledgeable in this field than other healthcare providers. As for practices, one in two surveyed customers (47%) did not always give feedback to their pharmacists about the outcomes after using CAM, 20% did not often ask the pharmacists about the safe and effective mode of use of the products and 28.1% did not discuss their medical history. For services offered by the pharmacist, the majority of participants reported receiving good education about the CAM product (87.1%), its side effects (87.1%) and mode of use (93.4%), while significant proportions of participants reported that pharmacists were not asking questions about their medical history before dispensing CAM products (22%) nor were they providing information on CAM-drug interactions (30%). Conclusions The results of this study highlighted important gaps between the perceptions of customers and the services they received from the pharmacists about CAM use. These findings could be used by concerned stakeholders, including public health authorities and educational bodies, to develop evidence-based interventions aimed at promoting the role of pharmacists in ensuring a safe and effective CAM use Lebanon.